Note on Chain Sequences of Laguerre and Romanovski-Laguerre Type Polynomials: Pradeep Malik, Nadeem Rao - Team, Support (Thai Journal of Mathematics, 2022)
In the last few years, the recurrence relations of classical orthogonal polynomials are useful in the studying of chain sequences andsome properties of Mass-Spring system. In this work, we discuss chain sequences of Laguerre and Romanovski-Laguerre type finite class of classicalorthogonal polynomials (COPs). We also introduce the application of chain sequences for discussing some properties of Mass-Spring system.